Catalunya i la Guerra de Successió d’Espanya : (1702-1714) - Alcoberro, Agusti (Acta Hispanica, 2014)
The War of the Spanish Successionaffected the entire continent of Europe directlyor indirectly. Within the Spanish Monarchy,Catalonia and the other states of the Crown ofAragon sided with Archduke Charles of Austria(Charles III), while Crown of Castile lent itssupport to Duke Philip of Anjou (Philip V).After the Peace of Utrecht, Cataloniaprolonged its resistance for 14 more monthsunder a republican government. At the end ofthe war, the victors imposed repression, exileand the end to the Catalan constitucions.